ความสัมพันธ์ระหว่างบุคลิกภาพในการประกอบอาชีพ รูปแบบการเรียนรู้ และการเผชิญกับปัญหาในผู้ใหญ่ตอนต้น - วีระยุทธ กุลสุวิพลชัย (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
The purpose of this research was to study relationships among personality, learning styles and coping of young adults. The subjects consisted of 300 young adults aged range between 22 to 40 years old, who had at least a Bachelor’s Degree, had an occupation, either in an organization or in their own business. The participants responded to a set of questionnaires measuring their career personality types based on Holland‘s concept (Holland, 1985), their coping styles based on Heppner, Cook, Wright, and Johnson’s concept (Heppner et al.,1995), and their learning styles based on Honey and Mumford’s experience learning approach (Honey & Mumford, 2006). The multiple regression analysis revealed that: 1. The enterprising, investigative, artistic, conventional, and realistic personality types significantly predicted the activists learning style (F = 35.233, p<.001) and accounted for 37.5 percent of the total variance of the activists learning style. 2. The investigative, conventional, and enterprising personality types significantly predicted the reflectors learning style (F = 46.600, p<.001) and accounted for 32.1 percent of the total variance of the reflectors learning style. 3. The conventional, investigative, and artistic personality types significantly predicted the theorists learning style (F = 72.997, p<.001) and accounted for 42.5 percent of the total variance of the theorists learning style. 4. The conventional and investigative personality types significantly predicted the pragmatists learning style (F = 32.643, p<.001) and accounted for 18.0 percent of the total variance of the pragmatists learning style. 5. The investigative type significantly predicted the reflective coping (F = 114.764, p<.001) and accounted for 27.9 percent of the total variance of the reflective coping. 6. The investigative personality type significantly predicted the suppressive coping (F = 123.456, p<.001) and accounted for 29.4 percent of the total variance of the suppressive coping. 7. The investigative, realistic and enterprising personality types significantly predicted the reactive coping (F = 15.091, p<.001) and accounted for 13.3 percent of the total variance of the reactive coping